A Mountain Caribou Strategy for British Columbia - McKinnon, G.A. (Rangifer, 1996)
Because of the declining population of mountain caribou in British Columbia and the increasing conflict between caribou management and timber harvesting, BC Environment recently has developed a new policy for mountain caribou management in the province. Three options were considered; 1) to manage habitats/populations to potential habitat suitability, 2) to manage habitats/populations to ensure that at least present levels are maintained and 3) to manage habitats/populations within a core area of the province only. The chosen strategy of managing habitats/populations to ensure that at least present levels are maintained is consistent with ministry goals and policies and will likely require that a network of protected areas, buffer areas and linking corridors be established. Initiatives to document existing mountain caribou distribution and to provide options for integrated caribou/timber solutions to management conflicts are ongoing. Successful implementation of this caribou management strategy will require the active participation of the Ministry of Forests since the protection of habitat is a shared responsibility.